Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan pada Kantor Pelayanan Pajak Pratama Jombang - Anandita, Septian Ragil; Hari, Rachmad; Mahendri, Wisnu (MAMEN: Jurnal Manajemen, 2022)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance at KPP Pratama Jombang. The method used in this study is a quantitative method. The population in this study amounted to 81 employees, while the sample amounted to 70 respondents using the Slovin formula. Data was collected using the questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results showed that part of the motivation variable had a positive but not significant effect on employee performance, while the work discipline variable had a positive and significant effect on employee performance. Simultaneously, the variables of motivation and work discipline have a positive and significant effect on the employee performance of KPP Pratama Jombang. The results of the analysis of the coefficient of determination obtained 0.538, or 53.8%, which means that the contribution of motivation and work discipline variables to employee performance is 53.8%, while the remaining 46.2% is influenced by other variables outside this regression equation or other variables not examined